Analysis Of Language In Its Use With Peers - Vika Fransisca (CV. Green Publisher Indonesia, 2023)
This study aims to determine the language style of peer speech sarcasm and to find out the meaning of peer speech sarcasm language style. In re-search, of course, there are research methods used, and the methods used by researchers in analyzing the sarcasm language style of peer speech are descriptive methods and the data analyzed is in the form of qualitative data. And the end of a study is the results of research, the results of research from this study are the meaning of sarcasm language style that is most often used to sarcasm language style which is rarely used by Students of Semester VII A Afternoon Indonesian Language and Literature Learning Year 2017-2018. There are several stylistic meanings of sarcasm that are most often used, namely the meaning of sarcasm that contains elements that are not pleasing to the ear, the meaning of sarcasm that contains elements of hurting the heart and the meaning of sarcasm that contains elements of banter/ spicy satire. Meanwhile, the language style of sarcasm that is rarely used, namely the meaning of sarcasm which contains elements of bitter reproach, the meaning of sarcasm which contains the element of speaking with bitterness and the meaning of sarcasm which contains elements of biting lips in anger.